To the fauna of chewing lice (Phthiraptera) of birds in the Lower Don region, Russia. Non-Passeriformes. Part 2 - O.D. Malysheva; A.V. Zabashta; O.O. Tolstenkov (Кавказский энтомологический бюллетень, 2020)
The aim of this work is to study the fauna of chewing lice in birds of the Lower Don region, Russia. The paper continues our previous investigations. Chewing lice were collected in 2001–2019. In total, 441 birds of 37 species from five orders of nonpasserines were examined: Anseriformes (4), Apodiformes (1), Charadriiformes (22), Columbiformes (5), Coraciiformes (2), Pelicaniformes (1) and Podicipediformes (2 species). Fifty four species of chewing lice belonging to the families Menoponidae and Philopteridae were collected from 322 birds and identified. Among them 16 species of chewing lice are recorded for the fauna of Russia for the first time: Bonomiella columbae Emerson, 1957, B. concii Eichler, 1947, Eidmanniella pellucida (Rudow, 1869), Meromenopon incisum (Giebel, 1874), Acidoproctus moschatae (Linnaeus, 1758), Campanulotes drosti Eichler, 1950, Capraiella subcuspidata (Burmeister, 1838), Columbicola bacillus (Giebel, 1866), Cummingsiella aurea Hopkins, 1949, Lunaceps actophilus (Kellogg et Chapman, 1899), L. falcinellus Timmermann, 1954, Pectinopygus gyricornis (Denny, 1842), Rhynonirmus helvolus (Burmeister, 1838), Quadraceps anagrapsus (Nitzsch, 1866), Q. phaeonotus (Nitzsch, 1866), Saemundssonia laticaudata (Rudow, 1869). Some of these species are illustrated in the paper. We also found one new host record: Saemundssonia lari (Fabricius, 1780) from Larus ichthyaetus Pallas, 1773. Austromenopon transversum Złotorzycka, 1968 and Actornithophilus piceus (Denny, 1842) are formally confirmed for recently separated two species of birds, Larus michahellis (J.F. Naumann, 1840) and Larus cachinnans (Pallas, 1811).